2022
DOI: 10.1002/adfm.202204459
|View full text |Cite
|
Sign up to set email alerts
|

Sustainable and Bench‐Stable Photoactive Aqueous Nanoaggregates of Cu(II) for ppm Level Cu(I) Catalysis in Water

Abstract: The nanomaterial containing amphiphile-stabilized mononuclear Cu(II) is developed. The material is characterized by various spectroscopic techniques, such as X-ray absorption spectrscopy (XAS), high-resolution transmission electron microscopy, nuclear magnetic resonance (NMR), UV-vis, and infrared spectroscopies. Since the structural data for the amphiphile-bound Cu(II) center is not available, a theoretical model based on DFT calculations is employed. The analyses based on NMR spectroscopic data, including th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 55 publications
0
10
0
Order By: Relevance
“…The hydrophobic pockets in these aggregates hold oleophilic substrates together to “dissolve” them in water, which can resolve the solubility issues of organic substrates in water . Therefore, commercially available surfactants such as sodium dodecyl sulfate (SDS), , hexadecyl trimethyl ammonium bromide (CTAB), , and polyoxyethylene 23 lauryl ether (Brij35) , and newly designed surfactants such as TPGS-750-M, PS-750-M, PTS, , and Nok , have been employed to promote a variety of reactions. The morphology of the aggregates is an important concern in the success of reactions because of the great relevance to solubilization and mass transfer of organic substrates.…”
Section: Introductionmentioning
confidence: 99%
“…The hydrophobic pockets in these aggregates hold oleophilic substrates together to “dissolve” them in water, which can resolve the solubility issues of organic substrates in water . Therefore, commercially available surfactants such as sodium dodecyl sulfate (SDS), , hexadecyl trimethyl ammonium bromide (CTAB), , and polyoxyethylene 23 lauryl ether (Brij35) , and newly designed surfactants such as TPGS-750-M, PS-750-M, PTS, , and Nok , have been employed to promote a variety of reactions. The morphology of the aggregates is an important concern in the success of reactions because of the great relevance to solubilization and mass transfer of organic substrates.…”
Section: Introductionmentioning
confidence: 99%
“…Combining this concentration effect with the shielding effect, we explored the stability of ligand- or antioxidant-free Cu( i ) species for one-pot azidation via S N Ar and Cu( i )-catalyzed azide-alkyne cycloaddition reaction. 19 Generally, the +1-oxidation state of Cu is unstable in water and requires a reductant or specific ligands or support to maintain that oxidation state. The addition of CuI and NaN 3 into an aqueous solution of PS-750-M, followed by visible light irradiation, generates a nanomaterial containing PS-750-M, Cu, and azide (Scheme 5).…”
Section: Design Applications and Insights Into Micellar Technologymentioning
confidence: 99%
“…In January 2020, she began her PhD studies under the supervision of Prof. Besides, it promotes metal-micelle binding, 13,14 enables the photoredox activity of Cu(II) for ppm level catalysis, 19 and provides shielding to water-sensitive reaction intermediates. 15,20 PS-750-M has a tertiary amide functional group connecting a polar mPEG chain with the non-polar hydrocarbon chain via a proline linker.…”
Section: Gaganpreet Kaurmentioning
confidence: 99%
See 1 more Smart Citation
“…Recently, Cu has reemerged as an alternative metal for metal-catalyzed cross-coupling reactions because of its cost-effectiveness, readily availability, and less toxicity. , Many studies have been reported for non-SM types of homogeneous ligand-stabilized Cu-catalyzed cross-coupling reactions. A survey of the literature shows that Cu­(I) complexes stabilized with β-diketones, phosphines, or 1,10-phenanthrolines were generally reported as the catalytical species in the Cu-catalyzed cross-coupling reactions. The chemical identity of the active Cu­(I) species depended on the oxidation states of the Cu precursors (i.e., Cu(0), Cu­(I), ,,, or Cu­(II) , ) and types of stabilizing ligands.…”
Section: Introductionmentioning
confidence: 99%